Estimating the German term structure - Sebastian T. Schich (Deutsche Bundesbank, 1997)
This paper introduces the Deutsche Bundesbank's new procedure for estimating the term structure of interest rates. It describes the basic methodological approaches used (Nelson and Siegel (1987) and Svensson (1994)) and some fundamental concepts which are important for estimating and interpreting such term structures. It also documents the application of the procedure to the prices of German Federal securities on a monthly basis from September 1972 to December 1996. The new procedure meets the requirements of monetary policy analysis as it represents a good compromise between, on the one hand, maximum approximation to the data and, on the other, smoothness of the curve and hence ease of interpretation for monetary policy purposes.
Keywords: 330; Zinsstruktur; Schätztheorie; Schätzung; Theorie; Deutschland